2015
DOI: 10.4028/www.scientific.net/amr.1112.271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Capacitive Deionization for Measurements of the Salt-Removal of NaCl, KCl and MgCl at Various Cell Voltages

Abstract: Carbon electrodes have been successfully synthesized and characterized for desalination system based on Capacitive Deionization (CDI) technology. The carbon electrodes were synthesized with an activated carbon (700 – 1400 m2/g), carbon black, glutaric acid and polyvinyl alcohol as a binder using cross-linking method at 120 °C. The study was to investigate salt removal percentage value of 0.1 M NaCl, MgCl and KCl using CDI cell. A solution with 0.1 M was supplied to the cell using a Boyu Submersible pump (model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Mg 2+ ion has the greatest electrostatic forces compared toNa + ion and K + ion,this is because the Mg 2+ ion ( r = 227 pm) has the width of hydration shell ( r) wider than Na + ion( r = 116 pm) and K + ion ( r = 74 pm) [14]. This fact is consistent with the results of the salt-removal levels in this study that stated the salt-removal percentage of KCl is greater than NaCl and MgCl.The same result has been reported by Diky et al [6]. The greatest value of salt-removal percentage was achieved at 64.95 % for KCl solution when the solution flowed to the CDI cell with the carbon electrodes prepared with freezing thawing for 4 cycles.…”
Section: Figure 4 CV Curves For Carbon Electrodes Prepared With Freesupporting
confidence: 88%
See 2 more Smart Citations
“…Mg 2+ ion has the greatest electrostatic forces compared toNa + ion and K + ion,this is because the Mg 2+ ion ( r = 227 pm) has the width of hydration shell ( r) wider than Na + ion( r = 116 pm) and K + ion ( r = 74 pm) [14]. This fact is consistent with the results of the salt-removal levels in this study that stated the salt-removal percentage of KCl is greater than NaCl and MgCl.The same result has been reported by Diky et al [6]. The greatest value of salt-removal percentage was achieved at 64.95 % for KCl solution when the solution flowed to the CDI cell with the carbon electrodes prepared with freezing thawing for 4 cycles.…”
Section: Figure 4 CV Curves For Carbon Electrodes Prepared With Freesupporting
confidence: 88%
“…The experiments were carried out for 6 h (3 cycles), each cycle consists of adsorption process for 1 h and regeneration process for 1 h. The experiments were repeated for 180 S/cm MgCl and KCl with same treatment. The salt-removal efficiency (%) can be calculated using equation as follows [5,6]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7][8], carbon electrodes were synthesized using the PVA binder through a cross-linking method. It was shown that the application of carbon electrodes having hydrophilic properties allowing to increase in the wetted surface area, enhances the efficiency of CDI process.…”
Section: Introductionmentioning
confidence: 99%
“…Radiasi elektromagnetik yang diemisikan oleh fosfor biasanya dalam rentang cahaya tampak, namun terdapat juga di daerah spektrum ultraviolet atau infra merah. Ion fosfor dapat tereksitasi oleh banyak jenis energi [7], contohnya fotoluminisensi tereksitasi oleh foton, katodoluminisensi oleh elektron, elektroluminisensi oleh tegangan listrik, triboluminisensi oleh energi mekanik (contohnya penumbukan), xray luminisensi oleh sinar-x, kemoluminisensi oleh energi dari reaksi kimia dan sebagainya [4,5]. Material semikonduktor ditandai dengan adanya band gap, yaitu celah pita energi yang terletak diantara pita valensi yang berisi elektron penuh dengan pita konduksi yang kosong seperti terlihat pada Gambar 1.…”
unclassified